Synthesis of ε-Fe2–3N Particles for Magnetic Hyperthermia - Soichiro Usuki; Tomoyuki Ogawa; Masaya Shimabukuro; Taishi Yokoi; Masakazu Kawashita (Journal of Functional Biomaterials)
Little research has focused on using iron nitride as thermoseed particles in magnetic hyperthermia, although magnetite (Fe3O4) is commonly used for this purpose. In the present study, we focus on iron nitride, especially ε-Fe2–3N. ε-Fe2–3N particles were synthesized from hematite (α-Fe2O3) and sodium amide (NaNH2) under various synthesis conditions, and the heat-generation properties of the particles were investigated to reveal the synthesis conditions that lead to particles with notable heat-generation performance. The particles synthesized at 250 °C for 12 h increased the temperature of an agar phantom by approximately 20 °C under an alternating magnetic field (100 kHz, 125 Oe, 600 s), suggesting that ε-Fe2–3N particles can be used for magnetic hyperthermia. The analysis results for the particles synthesized under different conditions suggest that the heat-generation properties of ε-Fe2–3N were affected by several factors, including the nitrogen content, particle size, crystallite size, saturation magnetization, and coercive force.